John Dewey. - Hampe, Michael (Klassiker auslegen., 2017)
In this series the most important works in the history of philosophy are discussed with cooperative commentary from internationally renowned philosophers. Each volume contains 12 to 15 essays, and follows the organizational structure of the discussed philosophical work. Essential reading for students and academics alike, the series elucidates the major themes in philosophy without the need for time-consuming consultation of secondary literature.